2017
DOI: 10.1097/ana.0000000000000368
|View full text |Cite
|
Sign up to set email alerts
|

A Dexamethasone-regulated Gene Signature Is Prognostic for Poor Survival in Glioblastoma Patients

Abstract: Background Dexamethasone is reported to induce both tumor-suppressive and tumor-promoting effects. The purpose of this study was to identify the genomic impact of dexamethasone in glioblastoma stem cell (GSC) lines and its prognostic value; furthermore, to identify drugs that can counter these side effects of dexamethasone exposure. Methods We utilized three independent GSC lines with tumorigenic potential for this study. Whole-genome expression profiling and pathway analyses were done with dexamethasone-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…The percentage of CSCs in tumors after DEX monotherapy was increased, in agreement with previous studies that demonstrated that treatment by single chemotherapy [42] or anti-angiogenic agents [43,44] may increase the population of CSCs through the generation of tumor hypoxia or other underlying mechanisms. Recently, DEX was found to induce a genetic program and CCAAT/enhancer binding protein beta (CEBPB) expression in glioblastoma stem cells, which is indicative of poor survival in glioblastoma patients [45] . These reported findings might explain why the proportion of CSCs in the DEX-treated group increased and confirm the necessity of the combined use of DEX and anti-CSC agents.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of CSCs in tumors after DEX monotherapy was increased, in agreement with previous studies that demonstrated that treatment by single chemotherapy [42] or anti-angiogenic agents [43,44] may increase the population of CSCs through the generation of tumor hypoxia or other underlying mechanisms. Recently, DEX was found to induce a genetic program and CCAAT/enhancer binding protein beta (CEBPB) expression in glioblastoma stem cells, which is indicative of poor survival in glioblastoma patients [45] . These reported findings might explain why the proportion of CSCs in the DEX-treated group increased and confirm the necessity of the combined use of DEX and anti-CSC agents.…”
Section: Discussionmentioning
confidence: 99%
“…Luedi MM reported that dexamethasone reduced temozolomide-induced apoptosis in glioma stem cells and reduced radiation sensitivity. Camptothecin is a potential neutralizer for dexamethasone-mediated adverse reactions [12]. Ortega-Martínez S has the opposite report in the study of astrocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…11 GBM patient-derived GSCs were cultured as described previously. 9,11,22 In brief, tumors were isolated, followed by enzyme treatment to obtain a single cell suspension that was then cultured in GSC media (DMEM/F12 containing 1× B27, 20 ng/ml EGF, and 20 ng/ml basic fibroblast growth factor). Two independent GSC lines (GSC3 and GSC6) were cultured as neurospheres for further scrutiny.…”
Section: Tissue Samples and Stem Cell Culturesmentioning
confidence: 99%
“…For the in vitro studies, we used 50 μM dexamethasone, a concentration that was within the wide range that was previously described for in vitro studies. 1,11 Neurospheres were exposed to Accutase cell detachment solution (EMD Millipore) for 3 minutes to obtain single cells and then cultured in GSC medium containing 50 μM dexamethasone (Sigma) for 6 days or GSC medium alone for the control, with media exchanged daily.…”
Section: In Vitro Modelmentioning
confidence: 99%
See 1 more Smart Citation